Diskriminasi Pada Etnis Tionghoa dalam Novel Miss Lu karya Naning Pranoto dan Novel Dimsum Terakhir karya Clara Ng - Sarah Sabillah; Liana Rochmatul Wachidah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2022)
This study aims to examine the comparison of discriminatory attitudes in Clara NG's Dimsum Terakhir novel and Naning Pranoto's Miss Lu novel. This study uses a theoretical approach to the sociology of literature and a descriptive qualitative approach. Data collection techniques are read, listen, and take notes. There are four data analysis techniques, namely (1) describing the data, (2) categorizing the data, (3) inferring the data, and (4) presenting the data. The results of the data analysis of this research show that in the novel Miss Lu and the novel Dimsum Terakhir, the picture of the government at that time had savage and discriminatory behavior towards ethnic Chinese. Ethnic factors cause the problem of all acts of ethnic Chinese discrimination. Discrimination treatment is carried out in five fields, namely (1) the political field, (2) the socio-cultural field, (3) the economic field, (4) the religious field (not appearing in the novel Dimsum Akhir), and (5) the education sector. The difference between the two novels is in the attitude and the way the main character responds to the discrimination that befell them.